Analisis Penyebab dan Konsekuensi Investasi di Indonesia Pasca Reformasi - Durratul Hikmah Fatus Solikhah; Angga Dwi Permadi; Muhammad Yasin (Student Research Journal, 2023)
Investment activity is considered one of the important factors to influence the economy. Investment has a positive relationship with state income. To achieve this economic growth, sources of financing are urgently needed to encourage the business world, one of which is through investment realization. There are many investment challenges that are crucial in efforts to increase economic growth and the process of recovering from the economic crisis in Indonesia. Analyzing the data in this study using a qualitative descriptive method, namely a research method with the data obtained is then arranged and described in such a way and systematically. The achievement of all goals must be based on the understanding that full economic recovery can only be achieved if there is improvement in all sectors of the Indonesian economy. Economic reform activities should not be limited to macroeconomic reforms.